Experimental Investigation on Mechanical Properties of Glass Fiber Hybridized Natural Fiber Reinforced Penta-Layered Hybrid Polymer Composite - Manjunathan Karthick; M. Meikandan; S. Kaliappan; M. Karthick; S. Sekar; Pravin P. Patil; S. Raja; L. Natrayan; Prabhu Paramasivam (International Journal of Chemical Engineering)
This article investigates and presents the upshots observed in the brook of hybrid composites especially, the current investigation focuses on the impact of fiber composition, sequence, and stacking pattern on composite mechanical Features. Five varied stacking sequences of hybrid composites encompassing laminates are used to create four classes of fiber with jute/bamboo/glass by utilizing a conscientious hand lay-up process with glass fiber-laced mats as their peripheral layer. For examination, fiber sequences are arranged in the combination of GJBJG, GBJBG, GJGJG, and GBGBG, where G, J, and B refer to glass fiber, jute fiber, and bamboo fiber, respectively. The position of fiber in the core layer is kept in a perpendicular direction with respect to adjacent piles which might be jute or bamboo fiber and the best position of fiber is considered due to the stacking order. Stress and strain were linear in the load versus deflection curves, and all of the samples failed quickly, it is observed that the sample containing a higher or considerable number of bamboo fiber layers exhibited increased strain and toughness. In comparison to other samples, embolism of glass fiber as the main and covering layer expressed a higher impact on the mechanical properties of the composites is observed in this investigation. The shattered sample morphology demonstrated that the matrix and reinforcements were compatible.